Hit over the head with hegemony: relations of power in Japanese and Taiwanese English school ads. Issue 1 (2nd January 2018) - Brown, Charles Allen
Abstract: With the commodification of English education in East Asian societies, a robust advertising industry has arisen to attract consumers. In the project described here, I engaged in a critical content analysis of over 1000 advertisements for English educational products and services collected in Japan and Taiwan. My focus was on how social groups are portrayed in the visual components of these Ads. Results indicate that this imagery served to place individuals into positions as 'owners' or 'consumers' of the commodity of English by virtue of factors such as national origin and race, while also sidelining others through invisibility. Such results imply the ongoing workings of powerful beliefs associated with English tending to cement traditional hegemonies. Thus, this research supports the call for heightened attention to critical visual literacy in education while at the same time suggesting a need to redouble efforts to disrupt relations of dominance within English education.